All together: Integrated care for youth with type 1 diabetes. Issue 6 (16th July 2021) - Versloot, Judith; Ali, Amna; Minotti, Simona C.; Ma, Julia; Sandercock, Jane; Marcinow, Michelle; Lok, Daphne; Sur, Deepy; de Wit, Maartje; Mansfield, Elizabeth; Parks, Sheryl; Zenlea, Ian
Abstract: Objective: We describe the implementation and evaluation of an integrated, stepped care model aimed to identify and address the concerns of adolescents with type 1 diabetes (T1D) associated with diabetes‐related quality of life (DRQoL), emotional well‐being, and depression. Research Design and Methods: The care model with 4 steps: (1) Systematic identification and discussion of concerns salient to adolescents; (2) Secondary screening for depressive symptoms when indicated; (3) Developing collaborative treatment plans with joint physical and mental health goals; and (4) Psychiatric assessment and embedded mental health treatment; was implemented into an ambulatory pediatric diabetes clinic and evaluated using quantitative and qualitative methods. Results: There were 236 adolescents (aged 13–18 years) with T1D that were enrolled in the care model. On average adolescents identified three concerns associated with their DRQoL and 25% indicated low emotional well‐being. Fifteen adolescents received a psychiatric assessment and embedded mental health treatment. Both adolescents and caregivers were appreciative of a broader, more holistic approach to their diabetes care and to the greater focus of the care model on adolescents, who were encouraged to self‐direct the conversation. Parents also appreciated the extra level of support and the ability to receive mental health care for their adolescents from their own diabetes care team. Conclusion: The initial findings from this project indicate the acceptability and, to limited extent, the feasibility of an integrated stepped care model embedded in an ambulatory pediatric diabetes clinic led by an interdisciplinary care team. The care model facilitated the identification and discussion of concerns salient to youth and provided a more holistic approach.